The function of Xenopus Bloom's syndrome protein homolog (xBLM) in DNA replication - Liao, Shuren (Cold Spring Harbor Laboratory Press, 2000)
The Bloom's syndrome gene (BLM) plays a pivotal role in the maintenance of genomic stability in somatic cells. It encodes a DNA helicase (BLM) of the RecQ family, but the exact function of BLM remains elusive. To study this question, we have cloned the BLM homolog of the frog Xenopus laevis (xBLM) and have raised antibodies to it. Immunodepletion of xBLM from a Xenopus egg extract severely inhibits the replication of DNA in reconstituted nuclei. Moreover, the inhibition can be rescued by the addition of the recombinant xBLM protein. These results provide the first direct evidence that BLM plays an important role in DNA replication, suggesting that Bloom's syndrome may be the consequence of defective DNA replication.